RELEVANCE OF ISSUES OF IMPLEMENTATION OF ADMINISTRATIVE REFORMS IN UZBEKISTAN - Shamuratov Jasur (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Currently, in our state, large-scale unnoticed reforms are being carried out in each area. After the crisis of the former Union, the newly independent state of Uzbekistan entered the world arena, after the independence, in order to carry out large-scale work to move to the market economy in our State, huge changes took place in the political, economic and spiritual spheres, and, moreover, in the administrative sphere, which became the basis for the development of these spheres. Due to the number of problems that Uzbekistan has been meeting for a quarter of a century, changes in many areas, as well as in the administrative sphere, have become a necessity, and the radical reform of this area has become a requirement of the period.